2014
DOI: 10.1130/gsatg203a.1
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting fractures and the formation of an iconic American landscape: Tuolumne Meadows, Yosemite National Park, USA

Abstract: Tuolumne Meadows, in Yosemite National Park (USA), is a large sub-alpine meadow in the Sierra Nevada Mountains. Immediately adjacent to Tuolumne Meadows-and underlain by the same bedrock lithology (Cathedral Peak Granodiorite)-are vertical rock faces that provide exceptional opportunities to climbers. While the presence of a broad meadow suggests bedrock erodibility, the vertical rock walls indicate bedrock durability. We propose that the Tuolumne Meadows's landscape is the result of variable glacial erosion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…In contrast to fluvial studies, where the importance of bedrock lithology in fluvial incision rates has been demonstrated (e.g., Stock and Montgomery, 1999), the explicit influence of rock type on glacial erosion is still little understood (Alley et al, 2003). Both chemical weathering rates (Anderson, 2005) and fracture intensity may also influence glacial erosion rates (Dühnforth et al, 2010;Becker et al, 2014). The degree to which the presence of subglacial meltwater and sediment at the bed affects both short-term and long-term glacial erosion is also still debated.…”
Section: Signals From the Source: The Role Of Glaciers In Sediment Prmentioning
confidence: 90%
“…In contrast to fluvial studies, where the importance of bedrock lithology in fluvial incision rates has been demonstrated (e.g., Stock and Montgomery, 1999), the explicit influence of rock type on glacial erosion is still little understood (Alley et al, 2003). Both chemical weathering rates (Anderson, 2005) and fracture intensity may also influence glacial erosion rates (Dühnforth et al, 2010;Becker et al, 2014). The degree to which the presence of subglacial meltwater and sediment at the bed affects both short-term and long-term glacial erosion is also still debated.…”
Section: Signals From the Source: The Role Of Glaciers In Sediment Prmentioning
confidence: 90%
“…Observations demonstrate that rates of quarrying depend on fracture density and orientation [Dühnforth et al, 2010;Krabbendam and Bradwell, 2011;Hooyer et al, 2012;Becker et al, 2014]. Hooyer et al [2012] compared the orientation of quarried lee surfaces to the direction of basal sliding.…”
Section: Fracture Distribution In the Bedrockmentioning
confidence: 99%
“…Becker et al . () show that areas of densely fractured rock in Tuolumne Meadows, USA exhibit low, flat surfaces, in contrast to the more sparsely fractured rock that forms high relief cliff faces and domes. They attribute this contrast to the dominance of glacial quarrying in densely fractured regions versus abrasion in sparsely fractured regions.…”
Section: Review Of the Influence Of Fractures On Geomorphic Processesmentioning
confidence: 99%
“…Becker et al . () found that extremely densely fractured zones caused preferential glacial quarrying in Tuolumne Meadows, where topographic highs correspond to areas lacking bands of fractured rock and lows correspond to areas that exhibit these fractured zones (Figure b). This provides direct evidence for Molnar et al .…”
Section: Review Of the Influence Of Fractures On Geomorphic Processesmentioning
confidence: 99%
See 1 more Smart Citation